KNOWLEDGE AND ATTITUDE OF PREGNANT WOMEN REPORTING AT TERTIARY CARE HOSPITAL - Sultana, Nighat; Fatima, Sadia; Muzaffar, Tabassum; Akram, Fahd (Pakistan Armed Forces Medical Journal, 2020)
Objective: To explore the knowledge and attitude of the pregnant women towards vaginal and caesarean delivery and association of socio-demographic factors with the knowledge and attitudes of the participants. Study Design: Cross sectional analytical study. Place and Duration of Study: Antenatal Clinic of Obstetrics and Gynaecology Department at a tertiary care hospital in Rawalpindi by self - administered interviews, from May 2018 to Oct 2018. Methodology: Three hundred and thirty-four women who attended antenatal clinic during the study period were interviewed using non-probability consecutive sampling method. The responses for chosen preferences were recorded on structured questionnaire after taking informed consent. All data was analysed using SPSS v.22. Results: The mean age of the women was 27.25 ± 4.235 years. Majority 291 (87.1%) of women interviewed had received formal education. Two hundred and thirty-two (69.5%) were unemployed and primigravida were111 (33.2%). The overall knowledge was found to be adequate in 204 (61.1%) participants for vaginal and in 149(44.6%) for caesarean section respectively. Two hundred and sixty seven (79.9%) of participants were willing for primary caesarean section but only 147 (44%) for elective repeat caesarean delivery. Only educational status (pvalue <0.001) was significantly associated with knowledge towards caesarean delivery. Conclusion: Pregnant women were having better knowledge of vaginal than caesarean delivery but they had positive attitude towards primary caesarean delivery due to fear of labour pains and vaginal birth after caesarean due to fear of pain during and after surgery.